Risk Factors Associated With Tuberculosis Among Children Aged 0–14 Years in Jambi City: A Case–Control Study - Maula, Nihlatul; Sitanggang , Hendra Dhermawan; Butar-Butar, Marta; Syukri, Muhammad (Jurnal Kesmas Jambi, 2026)
Tuberculosis (TB) among children remain a significant public health challenge in Indonesia, including Jambi City. Children aged 0–14 year are particularly susceptible to Mycobacterium tuberculosis infection due to their immature immune system. Several individual and environmental factors have been suggested to influence the occurrence of childhood TB, including nutritional status, household TB contact, BCG immunization, exposure to cigarette smoke, household crowding, and housing humidity. This study aimed to analyze risk factor associated with tuberculosis among children aged 0–14 years in Jambi City, Indonesia. An analytical observational study with a case–control design was conducted involving 96 participants, consisting of 32 TB cases identified through medical records from the selected primary healthcare centers and 64 controls selected through purposive sampling. Data were collected through structured interviews, document reviews, and direct household observations. Data were analyzed using univariate, bivariate, and multivariable logistic regression analyses. Ethical approval for this study was granted by the Health Research Ethics Committee of the Health Polytechnic of the Ministry of Health, Jambi (Reference No. LB.02.06/2/0002/2026). The findings revealed that at-risk nutritional status (Adj OR = 3.49; 95% CI: 1.22–10.51; p = 0.021) and household TB contact (Adj OR = 14.96; 95% CI: 4.80–55.25; p < 0.001) were significantly associated with childhood tuberculosis. In contrast, exposure to cigarette smoke, BCG immunization status, household crowding, and housing humidity were not significantly associated with childhood TB. These findings highlight the importance of strengthening household contact investigation and nutritional monitoring as key strategies for preventing and controlling tuberculosis among children.